Perbedaan Sikat Gigi Biasa Dengan Sikat Gigi Elektrik Terhadap Penurunan Debris Indeks Pada Murid Kelas V Madrasah Diniyah Islamiyah Kindaung Banjarmasin - Eddy Rahman; M. Bahrul Ilmi (Jurnal Kesehatan Indonesia, 2019)
Brushing teeth in a mechanical way is still considered the most effective way, even though the use of toothbrush with the help of special tools such as electric toothbrush. The purpose of this study was to find out there are differences in ordinary toothbrush with electric toothbrush against decreasing index debris in fifth grade students of MDIM Kindaung Banjarmasin. This type of research is a real experiment with the design of "control group pretest-post test design". In this study the research population & sample was 42 students in fifth grade (total sampling). Instrument of this research is observation, questionnaire with interview technique, analyzed by using T test (Independent Samples test). The results showed that there was a difference in the decrease in index debris using a ordinary toothbrush and a significant electric toothbrush, namely a decrease in using more electric toothbrush. It is hoped that this can be an input in implementing preventative programs for dental and oral diseases in students at the MDIM Kindaung Banjarmasin.